2016
DOI: 10.1371/journal.pone.0160181
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Non-Sustained Ventricular Tachycardia in Structurally Normal Hearts

Abstract: BackgroundThe impact of non-sustained ventricular tachycardia (NSVT) on the risk of thromboembolic event and clinical outcomes in patients without structural heart disease remains undetermined. This study aimed to evaluate the association between NSVT and clinical outcomes.MethodsThe study population of 5903 patients was culled from the “Registry of 24-hour ECG monitoring at Taipei Veterans General Hospital” (REMOTE database) between January 1, 2002 and December 31, 2004. Of that total, we enrolled 3767 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…141,144 The benefit of anticoagulating patients structural alterations that may be associated with the undesired outcome of major ventricular arrhythmias or sudden death ( Table 5). 151,152 There is no absolute threshold of the number of PVCs that can be used as a cut-off for underlying disease and hence should trigger further investigations. A study in apparently healthy athletes has shown that in those with >2000 PVC per day, there was a 30% risk of finding underlying heart disease.…”
Section: Consensus Statements Symbol Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…141,144 The benefit of anticoagulating patients structural alterations that may be associated with the undesired outcome of major ventricular arrhythmias or sudden death ( Table 5). 151,152 There is no absolute threshold of the number of PVCs that can be used as a cut-off for underlying disease and hence should trigger further investigations. A study in apparently healthy athletes has shown that in those with >2000 PVC per day, there was a 30% risk of finding underlying heart disease.…”
Section: Consensus Statements Symbol Referencesmentioning
confidence: 99%
“…Very rarely, otherwise 'benign' PVCs may give rise to polymorphic VT or ventricular fibrillation (VF) due to their short coupling interval. 152 Short-coupled PVCs impinging on the T wave may induce polymorphic VT/VF in a setting of ischaemia, electrolyte abnormalities, underlying LQTS, or early repolarization syndrome. This may also rarely occur in a 'normal' heart, sometimes called 'short-coupled form of torsades de pointes'.…”
Section: Consensus Statements Symbol Referencesmentioning
confidence: 99%
“…In addition, the HF patients with high‐PVC burden also had a higher prevalence of NSVT and multifocal PVCs, LA dilatation, and impaired exercise capacity compared with those with low‐PVC burden. The prevalence of NSVT and multifocal PVCs is associated with the development of cardiac death attributed to HF . LA overload due to LV dysfunction leads to LA enlargement, and LA remodeling is an independent predictor of mortality .…”
Section: Discussionmentioning
confidence: 99%
“…These clinical end points were investigated in detail based on initial identification through International Classification of Diseases, Ninth Edition, with reference to diagnostic codes or mention of an end point on discharge summary, and the database of the Collaboration Center of Health Information Application and National Health Insurance Research Database which had been previously validated. 9,[11][12][13][14] For detailed information, see the online-only Data Supplement. The overall end of follow-up was February 28, 2013.…”
Section: Follow-up and Event Ascertainmentmentioning
confidence: 99%
“…This methodology has been validated in our previous studies. [9][10][11][12] Furthermore, the institutional review board at Taipei Veterans General Hospital, Taipei, Taiwan, approved this study (Veterans General Hospital institutional review board number: 2013-08-002AC#1).…”
mentioning
confidence: 99%